Novel monoclonal antibody against integrin α3 shows therapeutic potential for ovarian cancer - Ke, Feng‐Yi (Cancer Sci, 2020)
Ovarian cancer has a high recurrence rate after platinum‐based chemotherapy. To improve the treatment of ovarian cancer and identify ovarian cancer‐specific antibodies, we immunized mice with the human ovarian carcinoma cell line, SKOV‐3, and generated hybridoma clones. Several rounds of screening yielded 30 monoclonal antibodies (mAbs) with no cross‐reactivity to normal cells. Among these mAbs, OV‐Ab 30‐7 was found to target integrin α3 and upregulate p53 and p21, while stimulating the apoptosis of cancer cells. We further found that binding of integrin α3 by OV‐Ab 30‐7 impaired laminin‐induced focal adhesion kinase phosphorylation. The mAb alone or in combination with carboplatin and paclitaxel inhibited tumor progression and prolonged survival of tumor‐bearing mice. Moreover, immunohistochemical staining of ovarian patient specimens revealed higher levels of integrin α3 in cancer cells compared with normal cells. By querying online clinical databases, we found that elevated ITGA3 expression in ovarian cancer is associated with poor prognosis. Taken together, our data suggest that the novel mAb, OV‐Ab 30‐7, may be considered as a potential therapeutic for ovarian cancer.